Targeted blockade of interleukin-8 negates metastasis and chemoresistance via Akt/Erk-NFκB axis in oral cancer. (June 2023) - Joshi, Swarali; Pandey, Ritu; Kumar, Ashok; Gupta, Vikas; Arya, Neha
Abstract: Background: The tumor microenvironment plays a significant role in tumor growth, metastasis and chemoresistance via dysregulated signaling pathways. Toward this, an inflammatory chemokine, interleukin-8 (IL-8), is overexpressed in various cancers and is involved in tumor progression and chemoresistance. However, the mechanistic role of IL-8 in mediating metastasis and chemoresistance in oral squamous cell carcinoma (OSCC) is not known. Methods and results: In the present study, we evaluated the effect of IL-8 in regulating metastasis as well as chemoresistance in OSCC cell lines. For this, IL-8 was blocked exogenously using neutralizing IL-8 monoclonal antibody and IL-8 levels were enhanced by exogenous supply of recombinant human IL-8 (rhIL-8) to OSCC cells. The epithelial-to-mesenchymal transition (EMT) was evaluated using qPCR, migration by scratch/wound healing assay and invasion ability using transwell assay. rIL-8 induced chemoresistance was studied by apoptosis assay and the nuclear localization of NFκB using immunocytochemistry. IL-8 was significantly overexpressed in OSCC patients and cell lines. While exogenous blockade of IL-8 significantly reduced EMT, migration and invasion potential in OSCC cells, IL-8 overexpression upregulated these cellular traits thereby confirming the role of IL-8 in OSCC metastasis. Exogenous blockade of IL-8 also reversed chemoresistance in cisplatin resistant OSCC subline via NFκB signaling. Conclusion: IL-8 plays a crucial role in OSCC metastasis and its targeted blockade can help in management of cisplatin resistance.